IMPLEMENTASI MODEL PROJECT BASED LEARNING PADA MINAT BELAJAR SISWA KELAS IV SDN MADE 1 SURABAYA MATERI BANGUN DATAR - Anut, Lestiana; Aditya Khoirun Nisa, Lita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the project-based learning model on the learning interests of fourth-grade students at SDN Made 1 Surabaya in the subject of plane geometry. This study used a descriptive qualitative approach. The subjects were 25 teachers and students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Project-Based Learning model was able to foster student learning interests, as demonstrated by several indicators: increased student attention during learning, active involvement, interest in the material, and a feeling of enjoyment in participating in the learning process. Furthermore, the teacher's role as a facilitator in guiding and directing students during the learning process also supported the successful implementation of the Project-Based Learning model. Based on these results, it can be concluded that the Project-Based Learning model is effective in increasing student learning interests in the subject of plane geometry composition in elementary schools.